لدينا العدد المركب :
ص=ب+ت ج = x+iyحيث ت^2=
-1
ن عدد صحيح أكبر من الصفر
ب عدد حقيقي
ومنه
لنعلم أن نه----ا ((1+(ت/ن )^ن ))^ب=
لما ن----->مالانهاية
نه------ا(1+(ب×ت)/ن )^ن=
لما ن---->مالانهاية
1 (تجب(1ب )+ت جب(1ب ))=
(ه^ت )^ب=(e^i)^ب. حيث ه= e= عدد أويلر
ومنه:
[(1+ (ت/(10^10 ))^(10^10 )]=
1 (تجب (1 )+ ت جب(1 ))=
ه^ت=e^i
ومنه :
((1+ت/10^10 )^10^10 )^π=
(تجب(1 )+ ت جب(1 ))^π=
ه^(ت×π)=
e^(iπ
ومنه : تجبπ +ت جبπ=ه^(تπ )
ومنه :
-1=ه^(تπ )
ومنه : ه^(تπ )=
e^(iπ)= -1
بن عبد الرحمان عبد الرحمان
Aucun commentaire:
Enregistrer un commentaire